Changing directions through VirtualPREX: engaging pre-service teachers in virtual professional experience - Gregory, S.; Dalgarno, B.; Campbell, M.; Reiners, Torsten; Knox, V.; Masters, Y. (University of Tasmania, 2011)
Many pre-service teachers currently undertake their professional experience with insufficient knowledge and confidence to handle unexpected teaching situations. VirtualPREX explores the experiences of 72 pre-service teachers who undertook a teaching role-play in a virtual world. The researchers discuss this opportunity for pre-service teachers to utilise new methods and avenues in a virtual world to both supplement their learning and undertake preparation for practical experience. Participation by pre-service teachers in role-play enables them to test and develop a better range of professional skills and acquire confidence in, and more realistic awareness of, their skills before being placed in real-life classrooms. Presented in this paper are the findings from a pilot of this study and pre-service teacher reactions to the role-play activity including whether they felt that it was helpful in preparing them for their upcoming professional experience placement.